APPLICATION OF E-LEARNING AND ARTIFICIAL INTELLIGENCE IN EDUCATION SYSTEMS IN INDONESIA - Dardya Putra Hastungkara; Endah Triastuti (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
Technology movement creates progressive impacts towards the development of communication network, computer, and the Internet. An innovation that is known as Artificial Intelligence (AI,) is one of many products. The usage of AI technology is predicted to expand globally, including in Indonesia. The influence of AI technology on improving the effectiveness of e-Learning concepts enables integration into the advancement of the education system in Indonesia. This study aims to explore the potential and impact of applying AI technology in e-Learning, and the readiness of various factors that influence the education system and Information and Communication Technology (ICT) in Indonesia. The discussion is based on secondary data and comprehensive observations of the prevailing learning structure.